Perubahan Perilaku Konsumen Dari Generasi Milenial Akibat Menggunakan Aplikasi Go-Food - Amalia Rosyadi Putri (Institut Agama Islam Syarifuddin Lumajang, 2019)
Industrialization, individualism, information, and investment support technological advancements that have triggered increasingly intense economic globalization. The benefits of the internet have brought many people connected to the internet and consumers are starting to make online purchases through the internet. Based on the results of a survey conducted by APJII 2016 it can be seen that the largest internet users in Indonesia are in the age range of 25-29 years and 35-39 years, which in that range is a range that is classified as young people or can be said to enter the